Synthesis and Characterization of Bromo-Substituted Salamo-Type Bisoxime Compounds Series - Xu, Li; Li, Na; Zhang, Yang; Wen, Na; Zhu, Li-Chun; Dong*, Xiu-Yan (Asian Journal of Chemistry, 2014)
Four novel bromo-substituted Salamo-type bisoxime compounds H2L1-H2L4 have been synthesized from 5-bromo-2-hydroxybenzaldehyde and 1,3-bis(aminooxy)propane, 1,4-bis(aminooxy)butane, 1,5-bis(aminooxy)pentane or 1,6-bis(aminooxy)henane in hot ethanolic medium, respectively and characterized by elemental analyses, IR, UV-visible spectra and 1H NMR spectroscopy.